2010
DOI: 10.2113/gssgfbull.181.6.477
|View full text |Cite
|
Sign up to set email alerts
|

Geodynamics of the France Southeast Basin

Abstract: We investigate the geodynamics of the Southeast Basin with the help of maps of the basement and of major sedimentary horizons based on available seismic reflection profiles and drill holes. We also present a study of the seismicity along the Middle Durance fault. The present seismic activity of the SE Basin cannot be attributed to the Africa/Eurasia shortening since spatial geodesy demonstrates that there is no significant motion of Corsica-Sardinia with respect to Eurasia and since gravitational collapse of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…In contrast, another study suggested the involvement of basement faults in the regional deformation [ Sébrier et al ., ]. However, earthquake nucleation to the west of the MDFZ [ Le Pichon et al ., ] allowed the observation that the active seismicity is located at a depth of less than 4 km to 5 km in the Mesozoic cover. For Le Pichon et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, another study suggested the involvement of basement faults in the regional deformation [ Sébrier et al ., ]. However, earthquake nucleation to the west of the MDFZ [ Le Pichon et al ., ] allowed the observation that the active seismicity is located at a depth of less than 4 km to 5 km in the Mesozoic cover. For Le Pichon et al .…”
Section: Discussionmentioning
confidence: 99%
“…The hydrocarbon potential of the SE Basin and the tectonic activity of the MDFZ have stimulated numerous stratigraphic, tectonic, and seismological studies of the Middle Durance Valley area [ Roure et al ., ; Benedicto Esteban , ; Roure and Colletta , ; Cushing and Bellier , ; Cushing et al ., ; Guignard et al ., ; Bellier et al ., ; Cushing et al ., ; Molliex , ; Le Pichon et al ., ; Rangin et al ., ; Molliex et al ., ]. Extensive seismic reflection surveys conducted by oil companies between 1971 and 1986 were mainly based on geophysical data [ Baudrimont and Dubois , ; Debrand‐Passard et al ., ; Bove , , , ], while some studies were focused on the deep structure and the stratigraphic and tectonic evolution of the SE Basin [ Benedicto Esteban , ; Cushing et al ., ; Le Pichon et al ., ; Rangin et al ., ; Molliex et al ., ]. These studies evaluated the thickness of the Meso‐Cenozoic sedimentary units, and they tried to image the depth of the Paleozoic basement.…”
Section: Introductionmentioning
confidence: 97%
“…This fault was mostly active as a normal fault during Paleozoic to Mesozoic times but also during Oligocene and Miocene times [Gigot et al, 1977]. The Mid-Durance fault zone is currently active as revealed by present-day earthquake distribution in the sedimentary cover [Cushing et al, 2008;Le Pichon et al, 2010;Cushing et al, 2014].…”
Section: Structure Of the Pyrenean-provence Forelandmentioning
confidence: 99%
“…This folding is related to the reverse faulting during the Alpine phase, that corresponds to inversion of Oligocene normal faults associated with 3000 m of total vertical offset [Roure et al, 1992;Benedicto, 1996;Cushing et al, 2008]. The resulting relief was further accentuated by salt tectonics associated with the thick deposits of rock salt in the core of the basin [Mercier et al, 1972;Le Pichon, 2010]. The Manosque Luberon fold is bordered to the west by a N-S fault that follows the Largue valley and that might correspond to the major structural boundary with the Grand Luberon.…”
Section: Structure and Relief Of The Luberonmentioning
confidence: 99%